Sending Out Alarms: A Perspective on Intercellular Communications in Insect Antiviral Immune Response - Wang, Fei (Frontiers in Immunology, 2021)
Viral infection triggers insect immune response, including RNA interference, apoptosis and autophagy, and profoundly changes the gene expression profiles in infected cells. Although intracellular degradation is crucial for restricting viral infection, intercellular communication is required to mount a robust systemic immune response. This review focuses on recent advances in understanding the intercellular communications in insect antiviral immunity, including protein-based and virus-derived RNA based cell-cell communications, with emphasis on the signaling pathway that induces the production of the potential cytokines. The prospects and challenges of future work are also discussed.